Some Negative Implications of Tourism on the Environment - Dobrescu, Codruta Mihaela; Turtureanu, Anca; Popa, Ionut; Dorobat, Leonard Magdalin (Journal of Danubian Studies and Research, 2024)
Tourism represents a sector with a rather low weight in Romania’s Gross Domestic Product, compared to the potential it would have. the tourist potential is very high, but little capitalized: balanced relief forms (mountains, hills, plains), the Danube Delta, Black Sea beaches, many mineral waters or muds or thermal springs with therapeutic properties, floristic, faunal, speleological objectives, cultural, culinary, business tourism, etc. The National Institute of Statistics shows that as a share of Romania’s GDP, tourism has evolved from 1.96% of GDP in 2014 to 2.98% in 2019, before the outbreak of the new SARS-CoV-2 coronavirus pandemic; for comparison with EU countries, according to Eurostat, in 2019, tourism generated 9.9% of the EU’s gross domestic product, and for 2023, over 10%. According to the National Strategy of Romania for the development of tourism 2023-2035, the growth of foreign tourist arrivals in the period 2022-2025 is forecasted to be 35% per year, and for each of the following years, from 2026 to 2035, an increase of 5% is estimated. These ambitious goals, even if they do not reach the level of other countries in the world with highly developed tourism, can often conflict with the environment. Even now, with less developed tourism, there are still environmental problems generated in many areas (some even protected areas); we exemplify the Bucegi Natural Park (the protected area where the anthropogenic impact is maximum), other mountain areas, the Danube Delta, and even caves, where the latter represent extremely fragile ecosystems. The solution is to manage such tourist sites on the basis of a plan that protects protected sites and makes them useful for tourism. It is important to specify the method of protection as well as the factors responsible for achieving that protection, established in correlation with the nature and dimensions of the tourist objective; for small ones, like a cave, a lake, etc., management is simpler. These problems are complicated when dealing with a large protected area, such as the Danube Delta, a national park, or a natural park, in which the organization of tourism exploitation and environmental protection is more complex and involves several levels: local, regional, and national. The negative influences of tourism on the environment are often more difficult to notice, especially by non-specialists, or are noticed after a long period when the degradation of ecosystems is high. This work presents such examples in the case of touristic objectives of great interest but affected by tourist activities. Finally, there is no conflict between the economic interest of making a profit, the exploitation of such an area, and the need to protect the environment of that area because, if at some point, the tourist objective were to be destroyed or degraded, then tourists would not still come, because there would be nothing left for them to visit.